Early leaving and the NEET agenda across the UK - Maguire, Sue [Verfasser] (My University, 2021)
“While measures to combat ‘Early Leaving’ (EL) have been widely adopted internationally, as a means of curbing rates of economic and social exclusion among young people, the term itself is not widely utilised across the UK. That is not to say that measuring and reducing the number of young people who drop out of education (or training) before meeting minimum age and/or qualification standards is not important. Rather, the emphasis has remained on maximising participation in learning and reducing NEET (not in education, employment or training) rates. Drawing on a recent policy review which was conducted in the UK, this article examines variations which exist between the four UK nations (England, Scotland, Wales and Northern Ireland) in terms of: compulsory education age requirements; capturing and measuring the number of young people who are defined as NEET and crucially, equality of access to support and intervention. It highlights that the four UK nations are increasingly pulling in different directions in terms of policy and practice. This has widespread implications for the opportunity structures that are available to all groups of young people across the UK.“ (authors‘ abstract; BIBB-Doku)
Keywords: P 2.1.1 Ohne Schulabschluss; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); I 2.2.1 Westeuropa; 370; Jugendlicher ohne Schulabschluss; Schulabbrecher; Jugendlicher ohne Ausbildungsvertrag; Ausbildungsabbruch; Bildungspolitik; England; Schottland; Wales; Nordirland; Vereinigtes Königreich